The Influence of Ethnomathematics-based Project-Based Learning on Students' Critical Thinking Skills in Elementary Schools - Nurdin Kamil; Aswasulasikin; Atika Susanti; Ilham Arya Susanto; Meilani Tirta Sari (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Critical Thinking (CT) is a high-level cognitive skill that is required and emphasized in the elementary mathematics curriculum. To reinforce the relevance and meaning of mathematical concepts, PjBL is integrated with the Ethnomathematics approach, which connects them to cultural contexts. This study aims to analyze the effect of applying the Project-Based Learning (PjBL) model integrated with Ethnomathematics on the flat building material of Rumah Limas on the improvement of critical thinking skills among elementary school students. This study used a quasi-experimental design involving an experimental group and a control group. Thedata collection instrument is a test of critical thinking ability through problem-solving. The study's results show that applying the Ethnomathematics-based PjBL model significantly improves students' critical thinking skills. The Independent Samples t-testshowed a significance value of 0.000 < 0.05, indicating a significant difference in the essential thinking skills of students taught with the PjBL model compared to those taught with conventional methods. This effectiveness is attributed to the model's success in requiring students to actively identify problems, provide logical reasons, and model geometric concepts from complex cultural objects, namely Rumah Limas. Ethnomathematics-based PjBL can be recommended as an effective pedagogical strategy in developing students' HOTS.